Spreading of α-Synuclein and Tau: A Systematic Comparison of the Mechanisms Involved - Vasili, Eftychia; Dominguez-Meijide, Antonio; Outeiro, Tiago Fleming (Frontiers in Molecular Neuroscience, 2019)
Alzheimer’s disease (AD) and Parkinson’s disease (PD) are age-associated neurodegenerative disorders characterized by the misfolding and aggregation of alpha-synuclein (aSyn) and tau, respectively. The coexistence of aSyn and tau aggregates suggests a strong overlap between tauopathies and synucleinopathies. Interestingly, misfolded forms of aSyn and tau can propagate from cell to cell, and throughout the brain, thereby templating the misfolding of native forms of the proteins. The exact mechanisms involved in the propagation of the two proteins show similarities, and are reminiscent of the spreading characteristic of prion diseases. Recently, several models were developed to the study the spreading of aSyn and tau. Here, we discuss the mechanisms involved, the similarities and differences between the spreading of the two proteins and that of the prion protein, and the different cell and animal models used for studying these processes. Ultimately, a deeper understanding of the molecular mechanisms involved may lead to the identification of novel targets for therapeutic intervention in a variety of devastating neurodegenerative diseases.